Research on the Research Status and Development Trend of Basketball Tactics in China in the Past 20 Years: Based on Cite Space Analyse - Yu, Shi (International Journal of Social Sciences and Public Administration, 2024)
This study uses China National Knowledge Infrastructure (CNKI) as the data source, the retrieval strategy is the subject word "basketball tactics", the literature time span is from January 2004 to May 2024, and 456 valid literature are finally obtained, and CiteSpace software is used to sort out and analyze the aspects of basketball tactics in China, aiming to explore the shortcomings of basketball tactics in China in theory and practice, and provide guidance and help for future research and practice. The results show that from the analysis of the number of articles on basketball tactics published in each year, the number of articles published in domestic journals on basketball tactics generally shows a trend of first increasing and then decreasing, reaching the highest value in 2017 and showing a wave-like decreasing trend after 2017, which to a certain extent reflects the decrease in the attention of domestic scholars in the field of basketball tactics in recent years, and should be maintained. The number of core authors of high-yield basketball tactics in China is small, and the number of authors published is relatively low. From the perspective of the distribution of research institutions, the authors and institutions are affected by the differences and majors of colleges and universities, and on the whole, colleges and universities with sports majors pay more attention to the field of basketball tactics research. From the perspective of the institutions that issued the papers, the degree of cooperation between institutions is low, the communication is not close enough, and only a few research institutions have cooperative relations, and it is necessary to strengthen the cooperation between institutions. Domestic research hotspots focus on basketball tactical theory research, applied research and teaching.